2018
DOI: 10.1080/13880209.2018.1529801
|View full text |Cite
|
Sign up to set email alerts
|

Anti-hepatofibrosis effect ofAllium senescensin activated hepatic stellate cells and thioacetamide-induced fibrosis rat model

Abstract: Context:Allium senescens Linn. (Liliaceae) (ASL) has been traditionally used in Korea and other Asian countries for improving digestive and liver functions.Objective: The anti-hepatofibrosis effect of ASL ethanol extract in cellular and experimental fibrosis rat model was investigated.Materials and methods:In vitro cell viability, cell cycle and apoptosis in hepatic stellate cells (HSCs) were studied using MTT assay, flow cytometry and Annexin V-FITC/PI staining. Thioacetamide (TAA; 200 mg/kg, i.p.)-induced li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…In the fibrotic liver, collagen is found to be expressed more due to the activated HSCs, but this will change to highly proliferative quiescent cells, followed by the deposition of collagen type I, which contains high amounts of fibrotic matrixes. This accumulated fibrotic matrix collagen can be quantified using the hydroxyproline assay [52][53][54]. Our study revealed that the HBV+TAA/EtOH group showed increased accumulation of collagen, while the high-dose-administered mouse group showed high expression.…”
Section: Plos Onementioning
confidence: 78%
“…In the fibrotic liver, collagen is found to be expressed more due to the activated HSCs, but this will change to highly proliferative quiescent cells, followed by the deposition of collagen type I, which contains high amounts of fibrotic matrixes. This accumulated fibrotic matrix collagen can be quantified using the hydroxyproline assay [52][53][54]. Our study revealed that the HBV+TAA/EtOH group showed increased accumulation of collagen, while the high-dose-administered mouse group showed high expression.…”
Section: Plos Onementioning
confidence: 78%
“…For example, it is reported that bulbs of A. sativum contain hundreds of phytochemicals including sulfur-containing compounds such as ajoenes ( E -ajoene, Z -ajoene), thiosulfinates (allicin), vinyldithiins (2-vinyl-(4H)-1,3-dithiin, 3-vinyl-(4H)-1,2-dithiin), sulfides (diallyl disulfide (DADS), diallyl trisulfide (DATS), and others that accounted for 82% of the overall garlic sulfur content [ 4 ]. Though Shin et al reported several distinct peaks including p -coumaric acid, chlorogenic acid, and rutin as major peaks compared with their respective standards in the HPLC analysis of A.S., the chemical composition and the biological effect of other Allium species have not been adequately investigated in different diseases [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Allium senescens L. (A.S.) also has been used as a diuretic, antidote, digestive, antiparasitic, and analgesic agent using the stems and leaves in herbal and folk remedies [ 5 ]. Though it was reported that A.S. can potentially be developed as therapeutic agents in the treatment of hepatic fibrosis [ 6 ], little is known about the bioactivity of A.S. against other diseases such as cancer.…”
Section: Introductionmentioning
confidence: 99%
“…But intraperitoneal injection provides more consistent results. Many researches have used Sprague–Dawley (SD) rats to induce liver fibrosis by intraperitoneal injection of TAA at a dose of 200 mg/kg twice a week for 12–13 weeks ( 30 , 31 ). Matsuo et al ( 12 ) used healthy macaca fascicularis to induce fibrosis model, dissolving TAA in normal saline and administrated three times a week at a dose of 100 mg/kg, and obtained that the TAA-induced model was superior to the CCl 4 model.…”
Section: Chemical Induction Methodsmentioning
confidence: 99%